Association between sleep regularity and arterial stiffness among middle-age adults in Southwestern China - Yuan-hao Shang; Da-qiang Liang; Xiao-ling Song; Xia Feng; Guang-yan Mao; Ting-ting Yang; Zi-yun Wang; Jun-hua Wang (BMC, 2024)
Abstract Background Sleep regularity has been linked to a risk of arterial stiffness (AS). However, the association between sleep regularity indicators, which reflect 24-hour sleep variability, and AS has not yet been examined. Methods We analyzed data from 516 adults, aged 40-65 years (the median age of 51 years), from the 'Follow-up Study of Sleep Characteristics and Chronic Diseases in the Middle-aged and Elderly Population in Guizhou Province'. Participants underwent assessments of AS (OMRON HBP-8000, baPWV ≥ 1400 cm/s) and sleep (wrist smart band (Honor band 5i) for ≥ 7 days). Logistic regression was utilized to evaluate the odds ratio (OR) and 95% confidence interval (CI) of the association between sleep regularity and AS. Results A total of 516 people were included in this study, of which 279 (54.07%) were in the AS group. The univariate results showed that the AS group (Median 71.18) had lower SRI compared to the No-AS group (Median 75.00) (p < 0.001). The multifactorial results showed participants with higher SRI scores were more likely to have a lower risk of AS compared to those with lower SRI scores (OR Q4 VS. Q1=0.46, 95%CI: 0.25-0.85, p = 0.013). The SRI effect was more pronounced in male (OR Q4 VS. Q1=0.28, 95%CI: 0.12-0.69, p = 0.005), snoring populations (OR Q4 VS. Q1=0.13, 95%CI: 0.04-0.48, p = 0.002), and non-retired populations (OR Q4 VS. Q1=0.45, 95%CI: 0.22-0.92, p = 0.028). Conclusions The present findings indicated that the effect between SRI and AS may be more sensitive than the standard deviation of sleep duration as well as the standard deviation of sleep onset.